Institutionalizing the farming systems perspective in multicommodity research institute: the role of systemsbased research groups - Spencer, D. (Cambridge University Press, 1991)
Research institutes in Africa have had limited success in producing new technologies appropriate to the needs of small farmers because of an inadequate understanding of small farmers' goals and resource limitations and over-reliance on the transfer of technologies from other regions. Farming systems research (FSR) is an effective way of improving the focus of scientists on the problems farmers face. Vertically segmented thematic research programmes make institutionalization of FSR difficult within multi-commodity research centres, particularly the International Agricultural Research Centres. The Farming Systems Research Group has proved effective at overcoming such difficulties at the International Institute of Tropical Agriculture. Its organization, operation and effects on the performance of the research programmes are described.